Método Ai Chi para crianças com asma: ensaio clínico controlado, randomizado e cego - Barbosa, Renata Ramos Tomaz (2019)
Objective: evaluate the effects of the Ai Chi method on lung function, clinical control, quality of life, anxiety symptoms and sleep disorders of children with asthma. Methods: A simpleblind randomized controlled clinical trial that evaluated children between 7 - 12 years of age with diagnosis of mild to severe asthma, randomized blocks: Experimental Group (EG) and Control Group (CG). Both received an educational intervention and the EG performed the Ai Chi method 2 times a week for 6 weeks, totaling 12 sessions. The outcomes were clinical control of asthma (Child Asthma Control Test -c-ACT and Asthma Control Test- ACT), spirometric variables, quality of life (Pediatric Asthma Quality of Life Questionnaire PAQLQ), anxiety symptoms (Spence Children’s Anxiety Scale- SCAS) and sleep disturbance (Sleep Disturbance Scale for Children -SDSC). Results: 23 children completed the protocol EG (n = 10) CG (n = 13). The groups did not differ in clinical control, lung function, quality of life, and anxiety symptoms. In the intragroup analysis, the EG presented a difference in total PAQLQ (p = 0.03, ES = 0.57) and, in the parent-report version, obsessive-compulsive problems – OCD (p = 0.029, ES = 0.81). The EG presented a high effect size for increase in FEV1 / FVC index (p = 0.208, ES = 3.75), and a moderate effect size for the reduction of anxiety symptoms in self-report child to social phobia (p = 0.637, ES = 0.55), obsessivecompulsive problems – OCD (p = 0.302, TE = 0.66), SCAS scoring (p = 0.201, ES = 0.57) and separation anxiety in parent-report version (p = 0.178, ES = 0.55). The CG presented a difference in the FEV1 / FVC index (p = 0.002, ES = 1.32) and the emotional domain of the PAQLQ (p = 0.018, ES = 0.30). The EG presented a significant increase of the sleep disturbances evidenced by the SDSC score (p = 0.03, ES = 0.43) and sleep–wake transition disorders –SWTD (p = 0.03, ES = 0.73). The CG presented a significant increase of disorders of initiating and maintaining sleep -DIMS (p = 0.027, ES = 0.60). In the intergroup analysis, the EG presented a significant increase of the SWTD (p = 0.02, ES = 0.66). Conclusion: The Ai Chi method had positive repercussions in quality of life and reduction of anxiety symptoms. However, there was an increase in the sleep-wake transition disorder in the children participating in the study. The results of this study may serve as a basis for considering the Ai Chi method as a treatment option used in the rehabilitation of children with asthma. However, the effects of this resource as a non-pharmacological treatment in children with asthma deserve further investigation. Study Registry: Clinical Trial Number: NCT03392129. Date of registration: January 5th, 2018.